Case Report: From lung to peritoneum: genomic and immunologic insights into a rare dual-site Corynebacterium striatum infection - Tang, Ying; Yan, Fei; Huang, Xincheng; Tang, Qin; Song, Guolin (Frontiers in Immunology, 2025)
Corynebacterium striatum is an emerging multidrug-resistant pathogen in immunocompromised patients. We report a 75-year-old male with paranoid schizophrenia on long-term clozapine who developed sepsis after gastric perforation repair. Within two days, genetically highly homologous Corynebacterium striatum strains were isolated from bronchoalveolar lavage fluid and ascitic fluid. Whole-genome sequencing revealed only 54 Single Nucleotide Polymorphisms (SNPs) differences, identical ermX-mediated resistance, and susceptibility to vancomycin and linezolid. Targeted therapy combined with drainage led to full recovery. This case highlights the potential for multi-site clonal infection via ICU environmental spread or endogenous translocation in the setting of postoperative immune suppression and invasive devices. Early multi-site sampling, molecular typing, and tailored antimicrobial therapy are essential, particularly in psychiatric patients requiring coordinated infection and psychiatric care.